Activation energy for the reverse eutectoid reaction in hypo-eutectoid Cu-Al alloys - Adorno, A. T. [UNESP]; Carvalho, T. M. [UNESP]; Magdalena, A. G. [UNESP]; dos Santos, C. M. A. [UNESP]; Silva, R. A. G. (Elsevier B.V., 2012)
The values of the activation energy for the reverse eutectoid reaction (alpha + gamma(1)) -> beta in the Cu-9 wt.%Al, Cu-10 wt.%Al and Cu-11 wt.%Al alloys were obtained using nonisothermal methods and considering two different reaction paths, one starting from annealed alloys and other from quenched alloys. The results showed that the activation energy for the reaction changes with Al concentration and strongly depends on the reaction path. The conversion dependence of the activation energy indicates a complex process comprising consecutive reactions which may be related with the dissolution of the pearlitic phase prior to the beta phase formation. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Nonisothermal kinetics; Eutectoid reaction; Cu-Al alloys